Planning as internal element of labour scientific organization of rear services specialists - Orel, О. V. (Honor and Law, 2019)
The general aspects of scientific organization of labour and possibility of introduction of her are reflected in activity of services of rear. Attention is accented on problem questions that arise up on the modern stage of development of the state.